The Role of Education in Raising the Efficiency of Human Resources use in Azerbaijan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Azerbaijan is currently experiencing improvements in its economic development model. Today, the vast majority of economic reforms have been completed in our country. The article considers investigated adequate mechanisms and identified directions of the use of human resources in the country in socio-economic challenges of the modern era.There were analyzed organizational and economic mechanisms of the search process of the reforms in education, raising the level of education, implementation of measures to form a modern vocational education system, the increasing investment which focuses on human development, adequate mechanisms of human capital development at the level of modern requirements.As one of the most noticeable areas of the modern era, it is the qualitative improvement the use of human resources in working places and working conditions. The article also includes the assessment of such factors.